Determinants of smoking initiation among women in five European countries: a cross-sectional survey - Del Mazo Sara S; Kralikova Eva; Haglund Margaretha; Allwright Shane; Dresler Carolyn; Heck Julia E; Oh Debora L; Stucker Isabelle; Tamang Elizabeth; Gritz Ellen R; Hashibe Mia (BMC, 2010)
Abstract Background The rate of smoking and lung cancer among women is rising in Europe. The primary aim of this study was to determine why women begin smoking in five different European countries at different stages of the tobacco epidemic and to determine if smoking is associated with certain characteristics and/or beliefs about smoking. Methods A cross-sectional telephone survey on knowledge and beliefs about tobacco was conducted as part of the Women in Europe Against Lung Cancer and Smoking (WELAS) Project. A total of 5 000 adult women from France, Ireland, Italy, Czech Republic, and Sweden were interviewed, with 1 000 from each participating country. All participants were asked questions about demographics, knowledge and beliefs about smoking, and their tobacco use background. Current and former smokers also were asked questions about smoking initiation. Basic statistics on the cross-sectional data was reported with chi-squared and ANOVA p-values. Logistic regression was used to analyze ever versus never smokers. Linear regression analyses were used to analyze age of smoking initiation. Results Being older, being divorced, having friends/family who smoke, and having parents who smoke were all significantly associated with ever smoking, though the strength of the associations varied by country. The most frequently reported reason for initiation smoking was friend smoking, with 62.3% of ever smokers reporting friends as one of the reasons why they began smoking. Mean age of smoking initiation was 18.2 years and over 80% of participants started smoking by the age of 20. The highest levels of young initiators were in Sweden with 29.3% of women initiating smoking at age 14-15 and 12.0% initiating smoking younger than age 14. The lowest level of young initiators was in the Czech Republic with 13.7% of women initiating smoking at age 14-15 and 1.4% of women initiating smoking younger than age 14. Women who started smoking because their friends smoked or to look 'cool' were more likely to start smoking at a younger age. Women who started smoking to manage stress or to feel less depressed were more likely to start smoking at an older age. Conclusions In all five participating countries, friends were the primary factor influencing ever smoking, especially among younger women. The majority of participants began smoking in adolescence and the average reported age of smoking initiation was youngest in Sweden and oldest in the Czech Republic.